2021
DOI: 10.1021/acs.joc.0c02504
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Free and Counterion-Bound Carbanions by Electrospray-Ionization Mass Spectrometry

Abstract: We propose electrospray-ionization (ESI) mass spectrometry as a robust and powerful method for the in situ analysis of carbanions. ESI mass spectrometry selectively probes the charged components of the sampled solution and, thus, is ideally suited for the detection of free carbanions. We demonstrate the potential of this method by analyzing acetonitrile solutions of 15 different carbon acids AH, whose acidities cover a range of 11.1 ≤ pK a(DMSO) ≤ 29.5. After treatment with KO t Bu as a strong base, all but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…This effect is most pronounced for analytes with nonpolar residues sprayed from polar solvents, [12] but less so for the THF solutions of the quite polar polymers probed here. In summary, we do not expect the ESI process to result in significant discrimination effects, in line with numerous recent examples of successful quantitative analyses by ESI‐MS, [13–15] including the demonstration of approximately linear correlations between sample concentrations and ESI‐signal intensities for carbanions [8] …”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…This effect is most pronounced for analytes with nonpolar residues sprayed from polar solvents, [12] but less so for the THF solutions of the quite polar polymers probed here. In summary, we do not expect the ESI process to result in significant discrimination effects, in line with numerous recent examples of successful quantitative analyses by ESI‐MS, [13–15] including the demonstration of approximately linear correlations between sample concentrations and ESI‐signal intensities for carbanions [8] …”
Section: Resultssupporting
confidence: 78%
“…In summary, we do not expect the ESI process to result in significant Chemistry-A European Journal discrimination effects, in line with numerous recent examples of successful quantitative analyses by ESI-MS, [13][14][15] including the demonstration of approximately linear correlations between sample concentrations and ESI-signal intensities for carbanions. [8] Comparison with NMR spectroscopy and SEC…”
Section: Analysis Of Carbanionic Oligomers By Esi-msmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinetics and laser flash photolysis experiments revealed that the average lifetime of such carbanions could be as short as 10 –11 s (Supplementary Note 1). While the existence of persistent carbanions in organometallics or in the preparation of stable carbanion salts for nuclear magnetic resonance and mass spectrometric characterization is often described in the literature, no general attempt was made so far to capture and isolate fleeting (metal-free) carbanion intermediate from a reaction medium for examining its time-dependent abundance. The lack of appropriate experimental probes may hide the actual reaction mechanism involving an elusive carbanion species in which some other plausible alternate mechanism is assumed to operate. , A recent report showed that the life expectancy of a carbanion intermediate generated by photolysis could be increased in dry zeolite by about 1 order of magnitude compared to that in the corresponding solution phase .…”
mentioning
confidence: 99%